Model Kepemimpinan Kiai Dalam Pesantren Salaf : Studi Kasus KH Taufiqurrahman di Pondok Pesantren Tasywiquth Thullab Salafiyah (TBS) Kudus - Safinah Safinah; Shodiqin Shodiqin; Achmad Sunani Miftachurrohman (STAI Darul Kamal NW Kembang Kerang, 2026)
The main problem of this research is how the leadership model and strategy of the kiai are able to maintain the sustainability of Salafi values ​​without hindering the development of Islamic boarding schools. This study aims to describe and analyze the leadership model and strategy of KH. Taufiqurrohman in maintaining and developing the Pesantafiyah Salafiyyah Tasywiquth Thullab in Kudus. This study uses a qualitative approach with a case study design. Data were collected through observation, in-depth interviews, and documentation studies with key informants consisting of kiai, pesantafiyah managers, ustaz, and students. Data analysis was carried out interactively through the process of data reduction, data presentation, and conclusion drawing, and its validity was tested through triangulation of sources and methods. The results show that the leadership of KH. Taufiqurrohman represents a charismatic and transformational leadership model based on moral-spiritual examples, human resource empowerment, and flexibility in decision-making. This leadership strategy is realized through independent and transparent management of educational funding and the development of an integrated curriculum that combines the traditions of Islamic boarding schools with modern formal education, thereby strengthening the sustainability and relevance of traditional Islamic boarding schools amidst the dynamics of contemporary Islamic education.